2017
DOI: 10.1128/mbio.02213-16
|View full text |Cite
|
Sign up to set email alerts
|

The Antituberculosis Drug Ethambutol Selectively Blocks Apical Growth in CMN Group Bacteria

Abstract: Members of the genus Mycobacterium are the most prevalent cause of infectious diseases. Mycobacteria have a complex cell envelope containing a peptidoglycan layer and an additional arabinogalactan polymer to which a mycolic acid bilayer is linked; this complex, multilayered cell wall composition (mAGP) is conserved among all CMN group bacteria. The arabinogalactan and mycolic acid synthesis pathways constitute effective drug targets for tuberculosis treatment. Ethambutol (EMB), a classical antituberculosis dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 54 publications
(92 reference statements)
8
38
0
Order By: Relevance
“…We found that the multilayered cell envelope of C. glutamicum and M. smegmatis is assembled sequentially at the septum from PG to MM during cytokinesis, unlike the apparently synchronous assembly observed during polar growth, thus suggesting that C. glutamicum and M. smegmatis use two different mechanisms (and machineries) for envelope assembly during polar growth versus cytokinesis. This conclusion was further supported by our observations with EMB treatment, after which polar PG synthesis and cell elongation were stalled while septal PG synthesis and septation were not affected, in agreement with the observations in a recent report 39 . The sequential assembly of septal PG and MM in the mycolata contrasts substantially with the synchronous assembly of septal PG and OM in Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the multilayered cell envelope of C. glutamicum and M. smegmatis is assembled sequentially at the septum from PG to MM during cytokinesis, unlike the apparently synchronous assembly observed during polar growth, thus suggesting that C. glutamicum and M. smegmatis use two different mechanisms (and machineries) for envelope assembly during polar growth versus cytokinesis. This conclusion was further supported by our observations with EMB treatment, after which polar PG synthesis and cell elongation were stalled while septal PG synthesis and septation were not affected, in agreement with the observations in a recent report 39 . The sequential assembly of septal PG and MM in the mycolata contrasts substantially with the synchronous assembly of septal PG and OM in Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Mycobacteria have been shown to expand from their poles ( Aldridge et al, 2012 ; Santi et al, 2013 ; Meniche et al, 2014 ; Thanky et al, 2007 ; Kieser and Rubin, 2014 ; Singh et al, 2013 ; Joyce et al, 2012 ) but published micrographs suggest that d -amino acid probes may label both the poles and sidewall of these organisms ( Meniche et al, 2014 ; Siegrist et al, 2013 ; Boutte et al, 2016 ; Botella et al, 2017 ; Schubert et al, 2017 ; Rodriguez-Rivera et al, 2018 ). Metabolic labeling can be achieved by a one-step process, in which the fluorophore is directly appended to the probe, or a two-step process in which a small chemical tag on the d -amino acid is detected by subsequent reaction with a fluorescent reactive partner ([ Siegrist et al, 2015 ], Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Because cell wall peptidoglycan synthesis is critical for bacterial replication, it is often used to localize the sites of growth and division. Intriguingly, d -amino acid probes, which in other species have been shown to incorporate into peptidoglycan ( de Pedro et al, 1997 ; Kuru et al, 2012 ; Siegrist et al, 2013 ), label both the poles and sidewall of mycobacteria ( Meniche et al, 2014 ; Siegrist et al, 2013 ; Boutte et al, 2016 ; Botella et al, 2017 ; Schubert et al, 2017 ; Rodriguez-Rivera et al, 2018 ). The localization of these molecules is supported by the detection of peptidoglycan synthetic enzymes at the mycobacterial cell tips and periphery ( Meniche et al, 2014 ; Joyce et al, 2012 ; Hett et al, 2010 ; Kieser et al, 2015a ; Plocinski et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A promising candidate for uncovering novel growth modes is the Gram-positive Corynebacterium glutamicum. C. glutamicum is broadly used as a production-organism for amino-acids and vitamins and also serves as model organism for the taxonomic related human pathogens C. diphteriae and Mycobacterium tuberculosis (12)(13)(14). The cell wall of Corynebacteria and Mycobacteria is a complex polymer composed of a classical bacterial peptidoglycan (PG) sacculus that is covalently bound to an arabinogalactan (AG) layer (15).…”
Section: Main Textmentioning
confidence: 99%